Phase formation in the SiC-Al₂O₃-ZrO₂ system during hot pressing by the method of electroconsolidation - Vovk, R.V.; Kislitsa, M.V.; Rucki, M. (Functional Materials, 2019)
The composition changes in the electroconsolidation of powdered ceramic materials based on SiC with Al₂O₃ and ZrO₂ contents are considered. Analyzed possible mechanisms of decrease of compaction ability due to chemical reactions and phase composition changes. The influence of nanodispersed powders on the formation of a eutectic composition during liquid-phase sintering and compaction of a material is shown. The nanocomposite material based on β-SiC, satisfying the requirements of a polyfunctional material obtained.